Interleukin-27 and interleukin-23 in patients with systemic lupus erythematosus: possible role in lupus nephritis. (May 2015) - Xia, LP; Li, BF; Shen, H; Lu, J
<x xml:space="preserve">Abstract</x> Objectives: To analyse the concentration of interleukin (IL)-27 and IL-23 in serum and urine of patients with systemic lupus erythematosus (SLE) compared with healthy controls (HC). Method: An enzyme-linked immunosorbent assay (ELISA) was used to analyse the serum and urine concentration of IL-27 and IL-23 from 50 patients with lupus nephritis (LN), 55 patients without LN, and 30 HC. The correlations between the levels of IL-27, IL-23, and disease activity, clinical parameters in SLE patients were analysed. Results: The levels of IL-27 and IL-23 increased significantly in the serum and urine of SLE patients with and without LN compared with HC. Moreover, urine levels of IL-27 and IL-23 were correlated with the renal SLE Disease Activity Index (rSLEDAI) score and 24-h urinary protein levels. After 6 months of immunosuppressive treatment, urine IL-27 expression rose significantly in SLE patients with LN. Conclusions: IL-27 and IL-23 may be involved in the pathogenesis of LN.